Stay : a novel - Gischler, Victor, 1969- (Thomas Dunne Books/St. Martin's Press, 2015)
"David Sparrow is an awesome stay-at-home dad. He gets his kids ready for school while his wife, Amy, commutes to New York City, where she was recently promoted to Deputy District Attorney. In fact, she just inherited a major case: prosecuting crime lord Dante Payne. Meanwhile, David is content chatting with the moms at school drop-off, making dinner at night, and doing housework. But when Dante Payne takes the fight directly to Amy, attacking her where she lives, David is forced to "reactivate" himself, revealing a history and deadly skill set his wife knew nothing about. And he'll do anything to protect his family. Part Taken, part First Blood, Stay is an action-packed, often hilarious, and hugely entertaining suburban thriller"--